Visual Communication Design for Animal Illustration Book Publication as Educational Media - Amanda Putri Cahya Wisesha; Deny Tri Ardianto (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This research aims to design books as an educational medium. The illustration book was chosen because it is considered quite effective and easy for learning, especially for children of 10-15 years old. The concept of designing this illustrated book uses a descriptive method with a qualitative approach. The object of this study is protected animals in East Kalimantan, while the subject is teenagers. The data collection technique uses surveys and literature studies. Next, a SWOT analysis was carried out. The results of the study showed that the results of a questionnaire from 51 students of SMPN 18 Balikpapan showed that the majority of respondents were 15 years old (54.9%), knew enough about protected animals (86.3%), and obtained information about animals in East Kalimantan from the internet (70.6%). Most students liked illustrated books, with 74.5% having read illustrated books and 58.8% interested in reading books about East Kalimantan animals. Respondents prefer books with soft covers and merchandise in the form of keychains. An illustrated book entitled